Health Workforce Migration in the Asia Pacific: implications for the achievement of sustainable development goals - Stephanie Short; Kanchan Marcus; Madhan Balasubramanian (ACHSM, 2016)
The maldistribution of health workers globally and within the Asia Pacific region remains problematic. While globalisation, and the increasing mobility of capital and labour, helps to reduce inequalities between countries, it increases inequality within countries. This study examines health workforce data and densities in the Asia Pacific region through a health workforce migration lens. The main implication relevant to achievement of sustainable development goals is the need for countries to work in a co-ordinated way in this region to increase substantially health financing and the recruitment, development, training and retention of the health workforce in developing countries, especially in least developed countries and small island developing states, most notably the Maldives, Timor- Leste, Kiribati, Samoa, Solomon Islands, Tuvalu and Vanuatu. Abbreviations: OECD - Organisation of Economic Co-operation and Development; SDG - Sustainable Development Goals; SIDS - Small Island Development States.